Paracetamol for osteoarthritis; is there a need for revision of guidelines? - Patil, P. T.; Murthy, M. B.; Pawar, M. P.; Ramanand, S. J.; Burute, S. R. (International Journal of Basic & Clinical Pharmacology, 2017)
Paracetamol (PCT) is the most commonly prescribed drug for pain of osteoarthritis (OA). Its advantage over non-steroidal anti-inflammatory drugs (NSAIDs) in terms of better gastrointestinal and renal safety had made this choice obvious especially in the elderly; a few years ago. Considering the current treatment guidelines (American College of Rheumatology, National Institute for Health and Care Excellence and European League against Rheumatism) which uphold PCT as the first choice drug for OA, a few studies have questioned the aforesaid advantage of PCT against its modest efficacy in patients with OA.